(untitled) (Italian Journal of Public Health, 2010)
Background: Young people are attracted by body art and consider it as a way of being “different”. Body art (tattoos, piercing, etc.) represents an important socio-cultural phenomenon which is not risk free for health. Existing literature, moreover, points out that deviant behaviours and unhealthy lifestyles are significantly associated with body art. Objective and methods: The research was aimed to describe the knowledge, attitudes, and practices of university students towards body art, highlighting the association between body art and some demographic variables, deviant behaviours, unhealthy lifestyles, knowledge of health risks and medical complications potentially involved. Data came from a cross-sectional study conducted on a sample, selected at random, of 1.200 undergraduate university students, (570, human sciences; 630, scientific areas). The instrument for the survey was a 21 item multiple choice questionnaire. Data was codified and statistical analysis was computed through Epi-Info and Openstat software. Results: Students from a scientific background showed a higher rate of interest, (p<0.01) for the argument of body art. About one third of the surveyed individuals had at least one body art. Cultural choice and gender was associated with body art. Males, especially from the scientific area, were more attracted by temporary body art, while females preferred permanent tattoos. Students from humanistic backgrounds were associated with one body art and those from a scientific area with more than one (p<0.01). Unemployment, lack of partnership and family attitude towards body art, were positively associated with students’ body art. Body art was strictly associated with different unhealthy lifestyles, such as drug, alcohol and tobacco consumption, problem gambling and sexual activity before 18 years of age. A relevant part of students considered piercing and tattooing as having no consequences for infections and/or disease. Conclusions: Body art was associated with unhealthy lifestyles and may be considered an indicator of risk taking behaviours. Individuals had no accurate idea of the consequences for their health and body, apart from a generic risk of infections. Education is a necessary tool for the modification of lifestyles and as a form of prevention ensuring the correct understanding and assessment of the health risk involved